Incidence and trend of preterm birth in China, 1990–2016: a systematic review and meta-analysis. Issue 12 (12th December 2020) - Jing, Shiwen; Chen, Chang; Gan, Yuexin; Vogel, Joshua; Zhang, Jun
Abstract : Objectives: To update the WHO estimate of preterm birth rate in China in 1990–2016 and to further explore variations by geographic regions and years of occurrence. Design: Systematic review and meta-analysis. Data sources: Pubmed, Embase, Cochrane Library and Sinomed databases were searched from 1990 to 2018. Eligibility criteria: Studies were included if they provided preterm birth data with at least 500 total births. Reviews, case–control studies, intervention studies and studies with insufficient information or published before 1990 were excluded. We estimated pooled incidence of preterm birth by a random effects model, and preterm birth rate in different year, region and by livebirths or all births in subgroup analyses. Results: Our search identified 3945 records. After the removal of duplicates and screening of titles and abstracts, we reviewed 254 studies in full text and excluded 182, leaving 72 new studies. They were combined with the 82 studies included in the WHO report (154 studies, 187 data sets in total for the meta-analysis), including 24 039 084 births from 1990 to 2016. The pooled incidence of preterm birth in China was 6.09% (95% CI 5.86% to 6.31%) but has been steadily increasing from 5.36% (95% CI 4.89% to 5.84%) in 1990–1994 to 7.04% (95% CI 6.09% to 7.99%) in 2015–2016. The annual rate of increase was about 1.05% (95% CI 0.85% to 1.21%). Northwest China appeared to have the highest preterm birth rate (7.3%, 95% CI 4.92% to 9.68% from 1990 to 2016). Conclusions: The incidence of preterm birth in China has been rising gradually in the past three decades. It was 7% in 2016. Preterm birth rate varied by region with the West having the highest occurrence.